PRIAYISME DAN KORUPSI KOLUSI NEPOTISME (KKN): STUDI STATUS GROUP DI KABUPATEN SLEMAN PROvINSI DAERAH ISTIMEWA YOGYAKARTA - Hariyanto, Hariyanto (Jurnal Aspirasi, 2012)
Aristocrat (priayi) closely related to the attributes of power, wealth, and prestige in the social structure of Java. This paper revisited the relationship between aristocrataristocracy and growing corruption, collusion and nepotism (CCN) prior to Indonesian Independence in 1945 to date from socio-culture point of view. The study showed that over those periods, there were relations between the aristocratic attributes of honor, power, and the practice of CCN at Sleman Regency